Aplicação da meta-heurística GRASP para o problema de corte de estoque bidimensional através de aplicativos CAD - Bianco, Clicéres Mack Dal (2010)
The PCE (Cutting Stock Problem) is to cut a set of objects available in stock to produce a quantity of items with specific sizes in order to optimize the raw material. Such problems have numerous industrial applications and has been widely studied in literature. The PCE's are classified as combinatorial optimization problems, because depending on the amount of requested items can be combined in numerous ways within an object forming an arrangement of cut. The number of possible combinations is, in practice, very high, requiring well-developed techniques are developed to determine an optimum arrangement. In defining the arrangements of cut is needed to graph the components of the problem and in this case, the tools used in the implementation must have the ability to manipulate geometric. In this paper, the combinatorial problem was approached from the GRASP heuristic technique and as a tool of manipulation was employed geometric applications deployed in an environment of Computer Aided Design (CAD). Furthermore, we proposed an integration of arrays of cutting systems with computer-aided manufacturing (CAM). The analysis of performance of the developed algorithm considers data provided by a furniture industry in the region of Santa Maria. The results obtained by the algorithm were compared to results generated by specialized software, consisting that the proposed method presents a similar performance, which demonstrates the feasibility of using CAD tools to implement solutions in the industry of PCE small and medium businesses.